First total synthesis, antitumor evaluation and target identification of mornaphthoate E: A new tubulin inhibitor template acting on PI3K/Akt signaling pathway - Peipei Shan; Tao Ye; Ying-De Tang; Hui Song; Chao Wang; Kongkai Zhu; Feifei Yang; Shi-Lei Zhang; Pei-Wen Su; Shuanhu Gao; Hua Zhang (Elsevier, 2024)
Mornaphthoate E (MPE) is a prenylated naphthoic acid methyl ester isolated from the roots of a famous Chinese medicinal plant Morinda officinalis and shows remarkable cytotoxicity against several human tumor cell lines. In the current project, the first total synthesis of (±)-MPE was achieved in seven steps and 5.6% overall yield. Then the in vitro anti-tumor activity of MPE was first assessed for both enantiomers in two breast cancer cells, with the levoisomer exerting slightly better potency. The in vivo anti-tumor effect was further verified by applying the racemate in an orthotopic autograft mouse model. Notably, MPE exerted promising anti-metastasis activity both in vitro and in vivo and showed no obvious toxicity on mice at the therapeutic dosage. Mechanistic investigations demonstrated that MPE acted as a tubulin polymerization stabilizer and disturbed the dynamic equilibrium of microtubules via regulating PI3K/Akt signaling. In conclusion, our work has provided a new chemical template for the future design and development of next-generation tubulin-targeting chemotherapies.